(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores the challenges faced by both teachers and students when it comes to teaching English grammar to non-native speakers. It highlights common difficulties such as understanding complex grammatical rules, overcoming differences between native languages and English, and dealing with errors in sentence structure, verb tenses, and word order. The article also examines effective teaching strategies, including the use of visual aids, interactive exercises, and contextual learning, to make grammar lessons more engaging and easier to comprehend. By addressing these challenges, the article aims to provide insights into how language instructors can help students master English grammar more efficiently and confidently.